Proterozoic granulite formation driven by mafic magmatism: An example from the Fraser Range Metamorphics, Western Australia - Clark, Christopher; Kirkland, Chris; Taylor, Richard (Elsevier BV, 2013)
Elevated heat flow and mafic magmatism during lithospheric extension have often been invoked as a mechanism to drive high-temperature low-pressure metamorphism that produces granulite facies mineral assemblages. Typically, however, evidence of the contemporaneous heat source, such as coeval mafic magmatism, is absent. In this study, we present pressure–temperature (P–T) pseudosection analysis combined with U–Pb isotopic data from zircon and monazite that constrain both the conditions and timing of granulite facies metamorphism in the Fraser Range Metamorphics of the Albany-Fraser Orogen in southern Western Australia. These results also elucidate the extremely rapid timing of, sequentially, deposition of sedimentary protoliths, mafic magmatism, partial melting, and metamorphism within the Fraser Zone during the Mesoproterozoic. The youngest detrital zircons, together with the magmatic ages of intrusive rocks, constrain the depositional age of the protoliths to the Fraser Range Metamorphics to between 1334 and 1293 Ma. Peak metamorphic conditions at c. 1290 Ma were c. 850 °C at pressures of 7–9 kbar.Peak metamorphism was followed by a period of isobaric cooling at pressures of c. 9 kbar. U–Pb zircon ages from leucosomes and metamorphic overgrowths in the metapelitic rocks indicate crystallization of partial melts at 1290 Ma, essentially coincident with the emplacement of mafic rocks at 1292 Ma. In situ analyses of both matrix hosted monazite and monazite inclusions in garnet yield ages between 1285 and 1268 Ma, with no significant age difference between monazite in the two textural positions. Cooling of the Fraser Zone below the Rb-Sr biotite closure temperature (~400 °C) occurred at 1260 Ma. Cooling and strengthening of the Fraser Zone rendered it less susceptible to subsequent tectonic events that affected rocks to the north and south of this resistant lozenge. Only rare geochronological evidence of later events can be resolved in recrystallised monazite rims dated at 1234 ± 17 Ma.